Internalisasi Nilai-Nilai Pancasila Dalam Kegiatan Ekstrakurikuler di SMPN 1 Tinambung - Manda, Darman; Arifin, Iqbal; Darmayanti, Dyan Paramitha (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the implementation of Pancasila values through extracurricular activities at SMPN 1 Tinambung and to identify the challenges and opportunities associated with its implementation. The research approach employed is a descriptive qualitative one, utilizing data collection methods that include observation, in-depth interviews, and documentation. The research informants consisted of four extracurricular advisors and three students who were selected purposively. Data validity was obtained through member checking and source triangulation techniques. The results showed that extracurricular activities at SMPN 1 Tinambung played an important role in internalizing Pancasila values among students. Values such as mutual cooperation, tolerance, deliberation, responsibility, humanity, and social justice were applied through student council activities, scouting, PMR (Youth Red Cross), and various school social activities. This implementation helps shape students' character to be disciplined, caring, and leadership-minded. However, the application of Pancasila values still faces several challenges, including limited resources, a lack of in-depth understanding among extracurricular advisors, and differences in students' levels of awareness and participation. This study also identified significant opportunities to enhance the internalization of Pancasila values by strengthening character-based extracurricular programs, utilizing digital technology as an educational medium, and fostering increased collaboration among schools, parents, and the community. The results of this study are expected to form the basis for the development of character education policies and strategies in secondary schools, so that Pancasila values are not only understood cognitively but also internalized and practiced in students' real lives.